2020
DOI: 10.1177/0193945920914593
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Outcomes and Predictors of Parenting Satisfaction in the Early Postpartum Period

Abstract: This study examined the relationships among parenting self-efficacy (PSE), social support, postnatal depression (PND), and predictors of parenting satisfaction in the early postpartum period using a cross-sectional exploratory quantitative design. The hypothetical model was tested among interrelated concepts of outcome variables among 250 parents (125 couples). The structural equation model revealed an adequate fit between the hypothesized model and the data. PSE and spousal support were found to be predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…Schoppe-Sullivan, Settle, Lee, and Kamp Dush (2016) reported that greater perceived supportive coparenting was associated with less parenting stress for new fathers, and with greater parenting satisfaction for fathers with high parenting self-efficacy. Similarly, a study of Singaporean families in the early postpartum period showed that support from partners was associated with both mothers' and fathers' higher parenting satisfaction (Shorey, Ying, & Yobas, 2020). Thus, we anticipated that new fathers who perceived greater gate-opening and less gate-closing behavior from mothers would be more satisfied and less stressed as parents.…”
Section: Family Relationshipsmentioning
confidence: 93%
“…Schoppe-Sullivan, Settle, Lee, and Kamp Dush (2016) reported that greater perceived supportive coparenting was associated with less parenting stress for new fathers, and with greater parenting satisfaction for fathers with high parenting self-efficacy. Similarly, a study of Singaporean families in the early postpartum period showed that support from partners was associated with both mothers' and fathers' higher parenting satisfaction (Shorey, Ying, & Yobas, 2020). Thus, we anticipated that new fathers who perceived greater gate-opening and less gate-closing behavior from mothers would be more satisfied and less stressed as parents.…”
Section: Family Relationshipsmentioning
confidence: 93%
“…Evidence from both HICs and LMICs also documents a protective effect against common perinatal mental health disorders in women [12,13]. Key mechanisms implicated in improving maternal and child health (MCH) are thought to be alleviating women's stress [11,14], facilitating their use of skilled antenatal (ANC), postnatal (PNC) and intrapartum care [15,16], and enabling them to adopt healthy lifestyles, for example, by reducing cigarette smoke [17]. The dynamics of social support by male partners may vary, including between HICs and LMICs; however, fostering their supportive role is important across the world.…”
Section: Introductionmentioning
confidence: 99%
“…This was done to compare the proportion of infants in each group who fell into the at-risk category for each domain. Established correlations between the main outcomes and covariates based on previous studies [36,37] were used to determine which covariates were needed to be statistically corrected for.…”
Section: Discussionmentioning
confidence: 99%